Analisis Manajemen Risiko pada Pelaksanaan Pembangunan Bangunan Hijau di Kota Semarang - Muhammad Afiq; Asri Nurdiana (Syntax Corporation Indonesia, 2024)
In implementing the development of green building projects, various obstacles often arise due to the risks that occur. Where this results in the performance, quality and achievement of work results not being achieved as expected. The aim of this research is to determine the dominant technical risk factors that occur during the construction of green buildings in the field and to determine the application of risk management in construction projects. In this research, risk identification, risk analysis and risk response were carried out in several green building developments in the city of Semarang. The research method used was by survey, distributing risk factor questionnaires and actions on risk factors to construction supervisor/management consultants. Assessment of the ranking of risk factor questionnaires and actions on risk factors using the Relative Importance Index (IKR).